A study of teaching experience and teacher-parent collaboration in managing students' disruptive behaviours - Adewale, Sulaimon; Moyo, Zvisinei (Jurnal Cakrawala Pendidikan, 2025)
Managing students' disruptive behaviours remains a critical challenge in secondary education, requiring effective strategies that leverage teachers' experience and collaborative efforts with parents. This study explores the influence of teaching experience and teacher-parent collaboration on managing disruptive behaviours among secondary school students in Nigeria. 367 teachers participated in the study, with data collected through a structured questionnaire. Statistical analyses, including one-way Analysis of Variance (ANOVA) and Pearson's Product-Moment Correlation, were employed to examine the relationships among the variables. The findings reveal that teachers' years of experience significantly impact their ability to manage students' disruptive behaviours, suggesting that seasoned teachers employ more effective behavioural management strategies. Conversely, a weak positive but non-significant correlation (r = 0.95, p = .068) was found between teacher-parent collaboration and disruptive behaviour management, indicating that while parental involvement may play a role, it does not strongly influence classroom management outcomes. These results highlight the necessity of structured professional development initiatives tailored to classroom behaviour management. Based on the findings, the study recommends implementing a teacher mentoring programme where experienced educators mentor their less experienced counterparts to enhance classroom management skills. This approach can foster a more structured, experience-driven response to disruptive behaviours, creating a more conducive learning environment. Future research should explore additional contextual factors, such as school policies and socio-economic influences, to provide a more comprehensive understanding of effective behaviour management strategies.